Age and sequence of emergence of permanent teeth in a population of Costa Rican schoolchildren = Edad y secuencia de erupción de la dentición permanente en una población de niños escolares en Costa Rica - Gutiérrez Marín, Natalia 1975-; López Soto, Andrea María 1987-; Castillo Rivas, Salvadora Jacqueline 1964- (2021)
The aim of this study was to determine the average age and sequence of eruption of permanent dentition in the school population of the province of Cartago, Costa Rica. Methods: A cross-sectional observational study included children between the ages of 5 and 12 from public and private schools. Clinical examination was performed, and the presence or absence of permanent teeth recorded. Statistical analysis: An estimation of means of eruption was used through binary variables, building the probabilities of the presence of a dental piece through a logistic regression. Results: 833 children were examined: 433 (51.90%) girls and 400 (48.10%) boys. The permanent teeth erupt first in the female sex; however, this difference is not statistically significant. The maxilla eruption sequence for girls was 6-1-2-4-3-5-7 on both sides; for boys, the sequence of eruption was 6-1-2-4-5-3-7 for the right side and 6-1-2-4-3-5-7 for the left side. In the jaw, the sequence in boys was 6-1-2-3-4-5-7, and in girls, 1-6-2-3-4-5-7. Conclusions: For the first time, at the Central American Level, the pattern of permanent dentition eruption could be established. The age of permanent dental eruption does not vary according to sex in this population.
El objetivo de este estudio fue determinar la edad promedio y la secuencia de erupción de la dentición permanente en la población escolar de la provincia de Cartago, Costa Rica. Metodología: se realizó un estudio transversal que incluyó niños con edades comprendidas entre los 5 y 12 años provenientes de escuelas públicas y privadas. Se realizó un examen clínico y se registró la presencia o ausencia de dientes permanentes. Análisis estadístico: se utilizó una estimación de las medias de erupción a través de variables binarias, construyendo las probabilidades de la presencia de una pieza dental por medio de una regresión logística. Resultados: se examinaron 833 sujetos: 433 (51,90%) niñas y 400 (48,10%) niños. Los dientes permanentes erupcionaron primero en el sexo femenino, sin embargo, esa diferencia no fue estadísticamente significativa. La secuencia de erupción maxilar para las niñas fue 6-1-2-4-3-5-7 en ambos lados; para los niños la secuencia fue 6-1-2-4-5-3-7 para el lado derecho y 6-1-2-4-3-5-7 para el lado izquierdo. En la mandíbula, la secuencia en los niños fue de 6-1-2-3-4-5-7-, y en las niñas fue de 1-6-2-3-4-5-7. Conclusiones: por primera vez a nivel de Centroamérica se pudo establecer el patrón de erupción de la dentición permanente. La edad de erupción dental permanente no varía según el sexo en esta población.
En revista Odóvtos, vol. 23, no.3 (septiembre-diciembre 2021)
Descripción basada en el contenido visto el 14 de noviembre, 2024
También disponible en formato HTML y EPUB